Studi Kasus Kesiapan Hybrid Working Kantor Pertanahan Kota Pekalongan Jawa Tengah - Maya Sofiana; Endang Supriyadi; Anita Maulina; Ahmad Junaedi; Rita Wahyuni (CV ODIS, 2022)
The purpose of this study was to determine the description of hybrid working readiness based on the Molla and Licker model, the advantages of efforts in hybrid working readiness, and the obstacles faced in the hybrid working readiness of the Land Office of Pekalongan City, Central Java. Research methods. This type of research uses the descriptive analysis method. Data collection techniques to obtain primary and secondary data are in-depth interview methods, observation or observation methods, and documentation. This study uses the guidance theory of Molla and Licker's model. The superiority of the efforts related to the readiness of Hybrid Working at the Land Office of Pekalongan City is the call center service and